Evidence of bias during liver transplant evaluation of non‐alcoholic steatohepatitis cirrhosis patients. (12th March 2019) - Danford, Christopher J.; Iriana, Sentia; Shen, Changyu; Curry, Michael P.; Lai, Michelle
Abstract: Background & Aims: Cardiovascular disease (CVD) is the leading cause of death among non‐alcoholic steatohepatitis (NASH) patients and a major source of post‐transplant mortality. We sought to examine the effect of comorbidities on listing for orthotopic liver transplant (OLT) in NASH patients. Methods: In this retrospective cohort study, we included all patients (n = 955) referred to Beth Israel Deaconess Medical Center for OLT between January 2002 and September 2011 and followed their outcomes through March 2018. Results: Compared with non‐NASH patients (n = 881), NASH patients (n = 74) were older, more likely female, more overweight, with higher rates of diabetes, hypertension and CVD. NASH patients were less likely to be listed for OLT (55% vs 68.9%, P  = 0.01) and were more often declined for 'medical comorbidities' (36.1% vs 15.7%, P  < 0.001). However, on multivariate analysis, the only significant predictors of listing were model for end‐stage liver disease (MELD) score (OR 1.04, P  = 0.01), HCC (OR 2.16, P  = 0.01), and diagnosis of non‐NASH cirrhosis (OR 2.56, P  = 0.003) while controlling for comorbidities. NASH patients declined for OLT died primarily from their liver disease and were not more likely to die from CVD than non‐NASH patients. There was no difference in outcomes of NASH vs non‐NASH patients on the waitlist and post‐transplant. Conclusions: This study demonstrates potential bias against NASH patients referred for OLT arising from heightened concern for comorbidities. Despite being declined for comorbidities, NASH patients are likely to die of their liver disease.